2014
DOI: 10.1002/phar.1482
|View full text |Cite
|
Sign up to set email alerts
|

Bedaquiline: A Novel Antitubercular Agent for the Treatment of Multidrug-Resistant Tuberculosis

Abstract: Bedaquiline is a diarylquinoline antitubercular drug with a novel mechanism of action against Mycobacterium tuberculosis. Bedaquiline works by inhibiting bacterial adenosine triphosphate (ATP) synthase and represents the first novel class of antituberculosis agents in more than 40 years. Bedaquiline is indicated for the treatment of multidrug-resistant tuberculosis (MDR TB) in combination with at least three other antitubercular drugs when no other effective regimen is available. The recommended bedaquiline do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
68
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(75 citation statements)
references
References 24 publications
0
68
0
Order By: Relevance
“…Bedaquiline distributes extensively into tissues and accumulates in cells by inducing phospholipidosis . It is unclear whether drug‐induced phospholipidosis causes toxicity, and the relationship between bedaquiline exposure and the extent of phospholipidosis is unknown.…”
Section: Should Bedaquiline Be Provided For All Patients With Mdr‐tb mentioning
confidence: 99%
“…Bedaquiline distributes extensively into tissues and accumulates in cells by inducing phospholipidosis . It is unclear whether drug‐induced phospholipidosis causes toxicity, and the relationship between bedaquiline exposure and the extent of phospholipidosis is unknown.…”
Section: Should Bedaquiline Be Provided For All Patients With Mdr‐tb mentioning
confidence: 99%
“…The authors reported a statistically significant reduction in the time of sputum--culture conversion (p < 0.001), which was shorter in the bedaquiline group, and in the percentage of sputum conversion, which was higher in the bedaquiline group at 24 and 120 weeks (p = 0.008 and p = 0.04, respectively) [55]. Similar data have been reported by the same authors in a previously conducted study (C208 stage 1) with a small sample size (47 patients) and a short therapy duration (8 weeks) [ Recently, a non-comparative, single-arm, open-label trial (C209) assessed the efficacy of bedaquiline in patients with MDR-TB with varying degrees of additional resistance who failed in previous therapies: the median time to sputum culture conversion was 57 days and consistent with both C208 stage 1 and stage 2 results [59,67,68].…”
Section: Performed Clinical Trialsmentioning
confidence: 84%
“…In 156 patients, proarrythmic potential was associated with erythromycin in 53% of cases and with CLR in 36% of cases, and 11% occurred in azalide-treated patients [93]. Since other MDR-TB drugs like moxifloxacin [94], delamanid [95] and bedaquiline [96] are also known to lengthen QT interval, adding macrolides to a MDR-TB regimen could increase the risk of cardiovascular events and mortality.…”
Section: Discussionmentioning
confidence: 99%